Strategi Pengembangan Bisnis Berbasis Ekonomi Kreatif: Studi Kasus UMKM Klaster Kuliner Jalan Pulosari dan Jalan Kawi Kota Malang - Manus, Victorio Chipta Gregory; Pangestu, Witjaksono Adi; Winarno, Agung; Rahayu, Wening Patmi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Although business development is a concept that has been applied in entrepreneurial practice, academic attention to its dynamics in the context of micro-enterprises is still very limited. This study aims to explore the core strategies in culinary UMKM business development and the challenges, by taking a case study of the culinary clusters on Jalan Pulosari and Jalan Kawi in Malang City. Through a qualitative approach with in-depth interviews with 30 micro-enterprises, this study identified three core business development activities that focus on utilizing business resources, as well as three supporting activities that function to secure and organize these resources. This finding indicate that all business development activities are centered on three main practices: leveraging, securing, and organizing resources, as explained in the resource-based view framework. In addition, this study reveals three contextual factors that influence UMKM development strategies: business sector, company age, and involvement in local business incubators. The theoretical contribution of this study lies in the development of a new conceptualization of business development in the microenterprise sector, which forms the majority of the global economic structure, but often fails to embark on a sustainable growth path. Practical implications are also offered, including strategies for time management and strengthening managerial capacity in response to perceived resource constraints. This study also proposes a further research agenda to explore the dynamics of business development in UMKM with more diverse qualities and contexts.